Improving Narrative Poetry Writing Through Film Media for Grade X-1 Students at YPKPM Christian High School Ambon - Lawalata, Foster Jouverd; Tabelessy, Novita; Frans, Thomas (Universitas Pattimura, 2021)
This research is driven by the issue of inadequate writing proficiency in the study of narrative poetry. The limited capacity to compose narrative poetry is attributed to several issues, including students' insufficient expressiveness in articulating thoughts derived from a teacher-provided notion, resulting in a passive learning experience, and students' poor performance in poetry writing. This research aims to equip educators with effective strategies to enhance the quality of narrative poetry writing instruction at YPKPM Christian High School in Ambon. The utilization of film media is anticipated to enhance pupils' proficiency in composing narrative poetry. Writing is a generative and expressive endeavor, according to Tarigan (1982:4). Narrative poetry is a form of poetry that conveys a story, tale, or the experiences of the poet (Gani, 2014:25). Film media can convey information, elucidate intricate concepts, and demonstrate processes, as it initiates learning through authentic scenarios or circumstances relevant to daily life. Arsyad (2002, p. 5). This research employs classroom action research (CAR) based on Susilo's CAR methodology, which comprises four stages: preparation, implementation, observation, and reflection. The four stages were executed in two study cycles, each concentrating on the evaluation of poetry writing in relation to themes, titles, and fidelity to film. This study was carried out at YPKPM Christian High School in Ambon, focusing on students from class X-1 as the subjects of research. This research aims to optimize the learning process and augment students' writing skills. The research findings indicate that the utilization of film media in narrative poetry composition enhances student engagement and facilitates the creation of quality poetry. This is apparent from the enhanced academic performance of the students. In Cycle I, only 11 individuals attained the minimal passing grade (KKM) of 69.00, although the anticipated KKM was 75.00. In Cycle II, the figure rose to 77.23.